2002
DOI: 10.1152/ajpheart.00468.2001
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptide gene expression in DOCA-salt hypertension after blockade of type B endothelin receptor

Abstract: Bianciotti, Liliana G., and Adolfo J. de Bold. Natriuretic peptide gene expression in DOCA-salt hypertension after blockade of type B endothelin receptor. Am J Physiol Heart Circ Physiol 282: H1127-H1134, 2002; 10.1152/ ajpheart.00468.2001.-We investigated the effect of longterm in vivo blockade of the ET-1 receptor subtype B (ET B) with A-192621, a selective ET B antagonist, on atrial and ventricular natriuretic peptide (NP) gene expression in deoxycorticosterone acetate (DOCA)-salt hypertension. In this mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In all ECG parameters (except for the P-wave amplitude) the DOCA-salt-neem group resembled the controls rather than the DOCA-salt group. The high amplitude of QRS complexes is common in DOCA-salt rats and has been attributed to cardiac hypertrophy which is a consequence of the induced hypertension (Matsumara et al, 1995;Bianciotti and De Bold, 2002). In our experiments, DOCA-salt accelerated conduction through the heart and increased the amplitude of the QRS complex and therefore the rate of contraction of the heart.…”
Section: Discussionsupporting
confidence: 60%
“…In all ECG parameters (except for the P-wave amplitude) the DOCA-salt-neem group resembled the controls rather than the DOCA-salt group. The high amplitude of QRS complexes is common in DOCA-salt rats and has been attributed to cardiac hypertrophy which is a consequence of the induced hypertension (Matsumara et al, 1995;Bianciotti and De Bold, 2002). In our experiments, DOCA-salt accelerated conduction through the heart and increased the amplitude of the QRS complex and therefore the rate of contraction of the heart.…”
Section: Discussionsupporting
confidence: 60%
“…Animal experiments conducted by Arnal et al (1992Arnal et al ( , 1993 revealed in rats that long-term (8 weeks) administration of N N -nitro-arginine methyl ester (l-NAME) significantly reduced the aorta cyclic guanosine monophosphate (cGMP) and elevated the arterial pressure, but did not change the left ventricular weight (LVW) and the LVW to body weight (BW) ratio. The absence of ventricular hypertrophy (VH) contrasted with results obtained in other models of experimental hypertension, in which long-term hypertension was accompanied by overt VH in essential, spontaneous, renovascular and DOCA-salt hypertension or hypertensive disease of primary aldosteronism (Bianciotti and De Bold, 2002;Ehamke et al, 1999;Hu et al, 1994b;Morton et al, 1993;Suzuki et al, 1988;Yokota et al, 1995;Yoshihara et al, 1996).…”
Section: Introductionmentioning
confidence: 73%
“…This study, in contrast, suggests that the extent of VH induced by chronic l-NAME administration is equally correlated with the steady and pulsatile hemodynamics. The impairment of large vessel properties suggests aortic stiffness and the pulse pressure with stiffness of large vessels was expected to increase (Bianciotti and De Bold, 2002;Hu et al, 1994a;Suzuki et al, 1988;Yoshihara et al, 1996). In these reports, the increase of pulse pressure ranged from 18 B A Fig.…”
Section: Discussionmentioning
confidence: 91%
“…One DOCA pellet was inserted subcutaneously between the shoulder blades, during which time the left kidney was also removed as described. 17,18 After recovery, rats were maintained on a 1% saline drinking water in place of tap water ad libitum. A control group of SD rats (nϭ6) underwent a sham surgical protocol, and cellulose was implanted instead of a DOCA pellet in parallel with the experimental group.…”
Section: Methods Animalsmentioning
confidence: 99%